Genome wide analysis of the complete GlnR nitrogen-response regulon in Mycobacterium smegmatis - Jenkins, Victoria A (BioMed Central, 2013)
BACKGROUND: Nitrogen is an essential element for bacterial growth and an important component of biological macromolecules. Consequently, responding to nitrogen limitation is critical for bacterial survival and involves the interplay of signalling pathways and transcriptional regulation of nitrogen assimilation and scavenging genes. In the soil dwelling saprophyte Mycobacterium smegmatis the OmpR-type response regulator GlnR is thought to mediate the transcriptomic response to nitrogen limitation. However, to date only ten genes have been shown to be in the GlnR regulon, a vastly reduced number compared to other organisms. RESULTS: We investigated the role of GlnR in the nitrogen limitation response and determined the entire GlnR regulon, by combining expression profiling of M. smegmatis wild type and glnR deletion mutant, with GlnR-specific chromatin immunoprecipitation and high throughput sequencing. We identify 53 GlnR binding sites during nitrogen limitation that control the expression of over 100 genes, demonstrating that GlnR is the regulator controlling the assimilation and utilisation of nitrogen. We also determine a consensus GlnR binding motif and identify key residues within the motif that are required for specific GlnR binding. CONCLUSIONS: We have demonstrated that GlnR is the global nitrogen response regulator in M. smegmatis, directly regulating the expression of more than 100 genes. GlnR controls key nitrogen stress survival processes including primary nitrogen metabolism pathways, the ability to utilise nitrate and urea as alternative nitrogen sources, and the potential to use cellular components to provide a source of ammonium. These studies further our understanding of how mycobacteria survive nutrient limiting conditions.